Prenatal Diagnosis of Structural Anomaly Among Singletons and Twins: Eight‐Year Experience in a Chinese Tertiary Center. (9th August 2022) - Ting, Yuan; Ting, Zhang; Fei, Zhao; Chun‐Fang, Li; Zhen, Han
Abstract : Objectives: This study was designed to reveal structural abnormalities in singleton and twin pregnancies in the Chinese population. Methods: This retrospective study spanned 8 years and included 1228 singleton pregnancies (112, 919 examinees) and 49 twin pregnancies (1865 examinees) with structural anomalies diagnosed by ultrasound. Detailed descriptions of anomalies, gestational weeks at diagnosis, and maternal age were recorded. The odds ratio was evaluated in twin pregnancies with detectable structural anomalies. Results: The annual average "ultrasound prevalence of fetal anomalies" among singleton and twin pregnancies were 1.09 and 3.06%, respectively. Mothers with twin anomalies were older ( P  < .001), and twin pregnancies were diagnosed with anomalies in earlier gestational weeks than singleton ( P  = .011). No differences were found in the types of anomalies between singleton and twin pregnancies. Central nervous system anomaly was the most common type in singleton and twin pregnancies. Twin pregnancies had higher rates of major anomalies than singleton (total OR 2.45), especially cardiovascular, central nervous, and gastrointestinal systems and ear/eye/face/neck disorders. Conclusions: Compared with singleton, twin pregnancies had higher odds of detectable structural anomalies. Twin pregnancies with structural anomalies were diagnosed at earlier gestational age and associated with older maternal age. Central nervous system anomaly was the most common type in singleton and twin pregnancies.